Studies on nutritional values of some culture-mushrooms (agaricus bisporus, agaricus campestris and aaaricus bitorauis) - Suzan Yalçın; O. Cenap Tekinşen (Eurasian Journal of Veterinary Sciences)
This study was carried out to investigate the nutritional values of culture-mushrooms and to obtain some basic information to increase their consumption.